Role of Genetic Sonogram After EIF Detection: A Cost-effectiveness Analysis [8P]. (May 2017) - Hacker, Francis; Griffin, Emily; Shaffer, Brian; Caughey, Aaron B.
Abstract : INTRODUCTION: Echogenic Intracardiac Foci (EIF) have been associated with trisomy 21 (t21) but in isolation, the positive likelihood ratio is low or nonsignificant. The 2014 Fetal Imaging Workshop recommends a completed targeted ultrasound (US) to identify other findings associated with t21. In light of US's low sensitivity, difficulty achieving adequate visualization due to maternal factors, and barrier to specialized care for rural populations, our goal was to evaluate outcomes and costs of this recommendation. METHODS: A decision-analytic model was constructed using TreeAge software and probabilities derived from the literature. The model compared targeted US with no further studies in women with both a negative quad screen and fetal EIF identified on screening US. This was stratified by maternal age. T21 Sensitivities for US and quad screen for women below and above 35 were assumed at 69%, 68%, and 91% and were examined in sensitivity analysis. Strategies were compared to generate an incremental cost-effectiveness ratio, with a threshold set to $100, 000 per QALY. RESULTS: Compared to no follow up, a targeted US in women less than 35 with an EIF and negative quad resulted in cost savings of $26, 725, 134 per 10, 000 pregnancies, a dominant strategy in cost-effectiveness. In women 35 or older, the targeted US strategy resulted in 55 additional QALYs with cost savings of $19, 692, 030 per 10, 000 pregnancies, also a dominant strategy. This remained cost effective to a risk for t21 of 0.0006 in fetuses with EIF. CONCLUSION: Our results indicate it is cost-effective to offer a targeted US when an EIF is visualized.